Evidence-based guideline implementation in low and middle income countries: lessons for mental health care. Issue 1 (December 2017) - Docherty, Mary; Shaw, Kate; Goulding, Lucy; Parke, Hannah; Eassom, Erica; Ali, Farnoosh; Thornicroft, Graham
Abstract Background There is a significant treatment gap in provision of effective treatment for people with mental disorders globally. In some Low and Middle Income Countries (LMICs) this gap is 90% or more in terms of untreated cases. Clinical practice guidelines (CPGs) are one tool to improve health care provision. The aim of this review is to examine studies of the effectiveness of evidence-based CPG implementation across physical and mental health care, to inform mental healthcare provision in low and middle income countries (LMICs), and to identify transferable lessons from other non-communicable diseases to mental health. Methods A systematic literature review employing narrative synthesis and utilising the tools developed by the Cochrane Effective Practice and Organisation of Care (EPOC) group was conducted. Experimental studies of CPG implementation relating to non-communicable diseases, including mental disorders, in LMICs were retrieved and synthesised. Results Few (six) studies were identified. Four cluster randomised controlled trials (RCTs) related to the introduction of CPGs for non-communicable diseases in physical health; one cluster-RCT included CPGs for both a non-communicable disease in physical health and mental health, and one uncontrolled before and after study described the introduction of a CPG for mental health. All of the included studies adopted multi-faceted CPG implementation strategies and used education as part of this strategy. Components of the multi-faceted strategies were sometimes poorly described. Results of the studies included generally show statistically significant improvement on some, but not all, outcomes. Conclusion Evidence for the effectiveness of interventions to improve uptake of, and compliance with, evidence-based CPGs in LMICs for mental disorders and for other non-communicable diseases is at present limited. The sparse literature does, however, suggest that multifaceted CPG implementation strategies that involve an educational component may be an effective way of improving guideline adherence and therefore of improving clinical outcomes. Further work is needed to examine cost-effectiveness of CPG implementation strategies in LMICs and to draw conclusions on the transferability of implementation experience in physical health care to mental health practice settings. Strategies to ensure that CPGs are developed with clear guidance for implementation, and with explicit, methods to evaluate them should be a priority for mental health researchers and for international agencies.